Sports and lateralization of visual spatial attention: A comparative study of practitioners of foot orienteering, judo wrestlers and non-athletes - Dimitrova, Ina (Psichologija, 2020)
Performance in all sports requires good spatial attention. This study investigates the impact of long-term sports training on lateralization of visual spatial attention and also explores if the type of sport (foot orienteering (FootO) vs. judo) could be related to differentiated effects on the pattern of lateralization. Thirty practitioners of FootO (aged 16-58 years, Mean age = 24.96±10.98; 16 males), 30 judo wrestlers (aged 16-60 years, Mean age = 25.96±10.61; 19 males), and 30 subjects who have never practiced any sport (aged 15-53 years, Mean age = 33.2±11.56; 13 males), were studied with a line-bisection task. All participants were right-handed and the athletes had at least 5 years of active sport practicing. Although the mean transection in the three groups was to the left of the true center regardless of the hand used suggesting right pseudoneglect, the accuracy of both hands was highest in the group of practitioners of FootO and lowest in the non-athletes group. Also, there were no between-hands differences in the accuracy among practitioners of FootO (t(30) = 0.062, p = 0.951), slightly better right hand accuracy in judo wrestlers (t(30) = 0.608, p = 0.548), and significantly better right hand accuracy in non-athletes (t(30) = -2.297, p = 0.029). In general, the results suggest that the active long-term training of any sport may affects functional brain organization of visual spatial attention towards its more balanced hemispheric presentation, but the type of sport is of great importance for the magnitude of the induced changes.